Improvements in mechanical, corrosion, and biocompatibility properties of Mg–Zr–Sr–Dy alloys via extrusion for biodegradable implant applications - Faisal Kiani; Jixing Lin; Khurram Munir; Cuie Wen; Yuncang Li (Journal of Magnesium and Alloys, 2023)
In this study, extrusion was performed on Mg‒Zr‒Sr‒Dy alloys for improving their mechanical, corrosion, and biocompatibility properties. Effects of extrusion and alloying elements on the microstructural characteristics, tensile and compressive strengths, corrosion behavior, and biocompatibility were investigated. The Mg‒Zr‒Sr‒Dy alloys were composed of an α-Mg matrix containing {101¯2} extension twins and secondary phases of intermetallic compounds Mg17Sr2 and Mg2Dy. Evolution of basal and rare earth (RE) textures was observed in the extruded alloys and an increase in Dy content to 2 wt.% resulted in texture randomization and strengthening of the RE component, mainly due to particle-stimulated nucleation and a change from discontinuous dynamic recrystallization to continuous dynamic recrystallization, which also led to an improved tension–compression yield asymmetry of 0.87. Extrusion of the alloys significantly enhanced their tensile and compressive properties due to improved distribution of alloying elements and formation of textures. Corrosion rates tested by hydrogen evolution testing, potentiodynamic polarization, and electrical impedance spectroscopy showed similar trends for each composition, and the lowest corrosion rate of 3.37 mmy−1 was observed for the Mg-1Zr-0.5Sr-1Dy in the potentiodynamic polarization testing. Dy2O3 was observed in the inner layers of the Mg(OH)2 protective films, whose protective efficacy was confirmed by charge-transfer and film resistances. A comparison among the minimum CRs observed in this study and previously studied as-cast Mg‒Zr‒Sr‒Dy and extruded Mg‒Zr‒Sr alloys, demonstrates that both the extrusion process and addition of Dy in Mg‒Zr‒Sr improved the CR. Similarly, extruded Mg–Zr–Sr–Dy alloys showed improved cell viability and adhesion of human osteoblast–like SaOS2 cells due to increased corrosion resistance and enhanced Sr distribution within the Mg matrix.